The weakening of the principle of criminal legality in the control of constitutionality of the colombian Constitutional Court (2012)
The PoliticalConstitution of Colombia is endowed with an extensive catalog of fundamental rights, guaranteed judicially, which are binding on all the state powers even for the legislative one, which are expressed through constitutional legal norms that pr